2021
DOI: 10.22454/fammed.2021.272274
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Family Medicine Residents in a Structured Patient Panel Reassignment Process

Abstract: Background and Objectives: The patient panels of graduating residents must be reassigned by the end of residency. This process affects over 1 million patients annually within the specialty of family medicine. The purpose of this project was to implement a structured, year-end reassignment system in a family medicine residency program. Methods: Our structured reassignment process took place from December 2017 through June 2020. Panel lists of current, active patients were generated and residents were responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Title and abstract review identified 294 potentially relevant articles that underwent full text review, with 74 including relevant data. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Title and abstract review identified 294 potentially relevant articles that underwent full text review, with 74 including relevant data. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 shows the findings for rules for adding and removing patients from panels and the frequency of updating panel lists as reported by 29 different health care systems and 5 empanelment guides. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 Details for each system or guide is provided in eTable 2 in the Supplement . Most organizations (29 [85.3%]) added patients to panels after 1 or more visits to primary care occurred (24 [70.6%] after 1 visit and 5 [14.8%] after several).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This process affects up to 1 million patients in the United States annually. 60 In the case of a clinic-first model, with approximately equal time in the FMP throughout residency, reassigning a graduating resident's panel to an incoming PGY1 resident is trivial. However, even in this situation, the program director may wish to engage in panel management as per ACGME requirements to balance the ages, genders, and…”
Section: Empanelment and Datamentioning
confidence: 99%